Pengaruh Promosi Melalui Media Brosur Terhadap Citra Merek (Studi Kasus pada PT Bogor Raya Development) (Studi Kasus pada PT Bogor Raya Development) - Sukartaatmadja, Iswandi; Suryanadi, Andri (Jurnal Ilmiah Ranggagading (JIR), 2011)
Promotion activity is important thing to communicate a products or services present to consument, and usually was a first step for company to show their products to people in wide ways, so products which has been produce can be well known and to compete with another competitor, this matter very realized by PT. Bogor Raya Development as property company. Therefore an important function of promotion, then PT. Bogor Raya Development have been initiative to make a media as be a part of it. There is a brochure which is has been choosen by PT. Bogor Raya Development as become one of promotion media, its because can be so simple and efficient to representative company products. This research attemted to know how far promotion influence pass by brochure media towards PT. Bogor Raya Development brand image, beside that to know how brand image of PT. Bogor Raya Development and also to know how tight between promotion by brochure towards PT. Bogor Raya Development brand image, this research was done in PT. Bogor Raya development which is located in Perumahan Danau Bogor Raya 16143. The result of this research shows that PT. Bogor Raya Development already done promotion activity by brochure, and result of analytical regression had a result for Y = 22.23 + 0.512(x) with brochure factor x = 1, is 22.742 and if brochure factor was increased by 100 times, constantly the value of Y = 73.43, from the analytical regression Ho has been refused and Ha has accepted because t observe (6.124) > t observe Â½ (1.661). The result of analytical correlation shows there is had a strong relation and positif between brochure and brand image, where value from analytical correlation was 0.512, after significance test has done result of t observe (6.124) > t table (1.661), this thing has been approved Ho which is made a statement there is no relation between brochure and brand image has been refused, and Ha which is made a statement there is a relation between brochure and brand image has been accepted. Beside that determinate coefisient to measure brochure contribute towards brand image have a result that brochure had only 27.7 % contribution and rest 72.3% contribution was influence by another factor